COVID-19 clinical outcomes and N-acetylcysteine (CoViNAC study): a GRADE compliant meta-analysis of randomized controlled trials with molecular docking and dynamics simulation studies with Mpro of SARS-CoV-2: COVID-19 and NAC (CoViNAC study) - Varikasuvu, Seshadri Reddy; Manne, Munikumar; Kumar, Subodh; Mudgal, Shiv Kumar; Raj, Vikash; Varshney, Saurabh; Gupta, Pratima; Grover, Ashoo; Goyal, Chanchal; Lal, Vanita; Singh, Harminder; MONA LISA; et al. (Cellular and Molecular Biology, 2025)
N-acetylcysteine (NAC) has been proposed as an adjuvant therapy for COVID-19, but evidence from randomized controlled trials (RCTs) remains inconclusive. This systematic review and meta-analysis evaluated NAC’s efficacy in improving mortality and recovery/discharge rates. Additionally, molecular docking and molecular dynamics simulation (MDMS) studies were conducted to assess NAC’s interaction with the SARS-CoV-2 main protease (Mpro), a key enzyme for viral replication. A systematic search identified 12 RCTs, with 11 trials (1125 patients) included in the mortality analysis. NAC significantly reduced mortality (RR=0.59, 95% CI 0.39–0.88, p=0.01; I²=62%), indicating a 41% decreased risk of death. Six RCTs (656 patients) showed improved recovery/discharge rates (RR=1.09, 95% CI 1.03–1.14, p=0.003; I²=0%). MDMS studies demonstrated stable NAC binding at the Mpro catalytic site, interacting with His41 and Cys145, crucial for enzymatic activity. These findings suggest NAC significantly improves clinical outcomes in COVID-19 and may inhibit viral replication by targeting Mpro. This integrated evidence substantiates NAC’s potential as a critical adjuvant therapy.